A study on the awareness among local residents towards green home concept / Azira Adzmi and Lizawati Abdullah - Adzmi, Azira; Abdullah, Lizawati (2018)
The objective of this study is to identify the level of awareness of potential homebuyers on green home concept among government staff in Seri Iskandar. This research also studies whether the potential homebuyers understand the benefit of having green homes. In Malaysia, the number of green developments is relatively below par as compared to other countries in Asian. One of the issues recognized through previous literature is the awareness among Malaysians. Malaysians may have little knowledge on the benefit of green building and most of them do not realize the importance of green home. The green home has a long-term benefit towards users and the environment, either from the economic and social perspective as well as environmental. This research was conducted among government staff in the District of Perak Tengah. A total of 120 questionnaires were distributed at two main administration buildings, Perak Tengah District Council and Perak Tengah District Administrative Complex. The data was analysed using SPSS Version 21.0 using descriptive statistics analysis. From the result of the analysis, majority of respondents are aware of the green home concept and they believed it can give the benefits into their life if they are apply the concept of green homes. It is recommended that further research to be done in other settings or areas.